Strengthening the government’s Supervision in Coal Mining as Enforcement of Administrative Laws in Post and Mining Activities - Lego Karjoko, Muhammad Adi Bagus Wicaksono, I Gusti Ayu Ketut Rachmi Handayani (International Journal of Advanced Science and Technology, 2020)
Many coal mining companies are reluctant to carry out reclamation and post-mining activities, which is causing harm to the environment, ecology and society. In this research, it is known that this is a result of the lack of intensity of supervision conducted by the government both before the Mining Business License (IUP) is issued or after the IUP is issued. First, in the case of supervision before the issuance of IUPs, it is known that many IUPs are issued without attaching reclamation and post-mining plans which are actually mandated by Article 99 (1) of Law 04/2009 which should be a reference for supervision of companies in conducting post-mining reclamation. Second, in the case of supervision after the issuance of IUP, it is known that the regulation regarding supervision, work mechanism, distribution of supervisors in mining areas, action models, is a problem that has never been well formulated to date. Then related to the large number of mining companies that have not provided reclamation and post-mining guarantee funds, this is known as a result of the regulation regarding withdrawal of post-mining Reclamation funds that are not clearly regulated in mining law in Indonesia.